Surgery vs medical treatment in the management of PFAPA syndrome: A comparative trial - Erdoğan, Fırat; Kulak, Kudret; Öztürk, Özmen; İpek Özahı, İlke; Ceran, Ömer; Seven, Hüseyin (Taylor & Francis Ltd, 2016)
Background: Periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis (PFAPA) syndrome is a common disorder in children but there is little or no consensus on its optimal diagnosis and management.Objectives: To compare the outcome of different management approaches - medical therapy or tonsillectomy.Methods: The medical records of children diagnosed with PFAPA between 2008 and 2013 were retrospectively reviewed according to the modified Thomas test criteria. Patients were divided into two groups: group 1 for medical treatment - corticosteroids, a single intramuscular injection of methylprednisolone, and group 2 for surgery - tonsillectomy alone or tonsillectomy plus adenoidectomy .The course of the disease including the number and duration of episodes and the presence of remission, was documented.Results: 105 patients (30 in group 1, 75 in group 2) met the study's inclusion criteria. Groups 1 and 2 were followed up for a mean (SD) of 23.6 (11.0) and 24 (10.3) months, respectively. At the end of the follow-up period, the number of episodes was 5.8 (6.3) vs 1.8 (1.9) (P<0.01) and their duration was 2.2 (1.3) vs 1.1 (0.8) days (P=0.03), both of which were significantly lower in group 2.The need for hospitalization during this period was significantly lower for group 2 at 1.1 (2.0) vs 0.1 (0.3) (P<0.01) and the remission rate in group 2 was significantly higher than in group 1 (98.6% vs 56.6%, P<0.01).Conclusion: This study demonstrated that surgery is superior to medical treatment for PFAPA in terms of increased remission rates and a decrease in the number and duration of episodes.
WOS: 000390990500004
PubMed ID: 26256936
Keywords: Medical Treatment; Periodic Fever; PFAPA Syndrome; Surgery